The competitive role of balsam fir (Abies balsamea) in the forest understory at the deciduous/boreal forest ecotone, Ontario, Canada. - Loesch, Jameson L. (Northern Illinois University.Geography., 2010)
Sorry, the full text of this article is not available in Huskie Commons. Please click on the alternative location to access it. 133 p. As the climate changes, balsam fir (Abies balsamea) and other boreal forest species in North America will have to deal with an influx of hardwood tree species attempting to expand their ranges northward. The success of this migration into the boreal forest and its influence on the ecosystem largely depends on the competitive relationship between balsam fir and these hardwood species in the forest understory. To gain insight into the future role of balsam fir in the forest ecosystem of this region, this study examined how stand structure, balsam fir photosynthesis rates, and nitrogen concentrations varied between different forest types at the deciduous/boreal forest ecotone in Lake Superior Provincial Park, Ontario, Canada. Findings indicate that despite the benefit of growing in a deciduous forest environment on photosynthesis rates, balsam fir lacks the competitive ability to impede the northward migration of these hardwood tree species, and will slowly lose its territory.